Extracting planetary waves from geomagnetic time series using Empirical Mode Decomposition. (July 2015) - Frühauff, Dennis; Glassmeier, Karl-Heinz; Lockwood, Michael; Heyner, Daniel
Abstract: Empirical Mode Decomposition is presented as an alternative to traditional analysis methods to decompose geomagnetic time series into spectral components. Important comments on the algorithm and its variations will be given. Using this technique, planetary wave modes of 5-, 10-, and 16-day mean periods can be extracted from magnetic field components of three different stations in Germany. In a second step, the amplitude modulation functions of these wave modes can be shown to contain significant contribution from solar cycle variation through correlation with smoothed sunspot numbers. Additionally, the data indicate connections with geomagnetic jerk occurrences, supported by a second set of data providing reconstructed near-Earth magnetic field for 150 years. Usually attributed to internal dynamo processes within the Earth's outer core, the question of who is impacting whom will be briefly discussed here. Abstract : Highlights: EMD is used as an alternative tool to analyze geomagnetic time series. Planetary wave modes of 5-, 10-, and 16-day mean periods are extracted from the data. The amplitude modulation of the waves shows correlation with sunspot number data.